The big question: why do change initiatives in education often fail to yield desired results? - Hope Nudzor (Educational Futures)
Although a wealth of fascinating literature on change management abounds in education, there is credible evidence to suggest that a lot of initiatives introduced with the view to bringing about improvement in pupils’ learning outcomes often fail to yield intended results. By reviewing literature from disparate research sources, this article unearths the causal factors of this change conundrum while exemplifying implicitly the kinds of strategic work that needs to be done order to bring about the desired outcomes of change. The inherent criticisms of the problem-solving approach to change management adopted by the article are also discussed. The article contends that the approach to change management it adopts is illuminating for the following two reasons. First, the approach propels ‘effective leadership’ as a crucial ingredient for a successful change strategy. Second, it advises against adopting the straight-jacket of external accountability that favours the imposition of change from the ‘outside’.